2017
DOI: 10.1007/s00482-017-0206-1
|View full text |Cite
|
Sign up to set email alerts
|

Komplementäre und alternative Verfahren beim Fibromyalgiesyndrom

Abstract: Meditative movement therapies (e.g. qi gong, tai chi and yoga) are strongly recommended. Acupuncture and weight reduction in cases of obesity can be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 19 publications
0
4
0
5
Order By: Relevance
“…Qi Gong also corrects the posture of the spine and the pelvis and prevents stagnation of the energy in the joints [29]. On this basis, scientific research suggests that low-intensity aerobic exercise and meditative movement therapies, such as Qi Gong, are recommended for the treatment of fibromyalgia patients, as they improve their symptoms and quality of life [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Qi Gong also corrects the posture of the spine and the pelvis and prevents stagnation of the energy in the joints [29]. On this basis, scientific research suggests that low-intensity aerobic exercise and meditative movement therapies, such as Qi Gong, are recommended for the treatment of fibromyalgia patients, as they improve their symptoms and quality of life [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Em 2017, foi confeccionado um Guideline sobre Terapias Alternativas e Complementares para a Síndrome de Fibromialgia, a partir da revisão sistemática e metanálise de estudos clínicos. As recomendações seguem o padrão: "Fortemente recomendado, recomendação em aberto, sem recomendação positiva ou negativa e recomendação negativa" [17]. Foi elaborado um quadro ilustrativo para melhor compreensão das informações encontradas para posterior análise, conforme Quadro 1.…”
Section: Resultsunclassified
“…According to these results, it was shown that functional mobility decreased the falling risk with Tai Chi in functional measurements and minimized difficulties in performing essential daily physical activities [35]. The German Pain Society 2017 guideline in "Complementary and alternative procedures for fibromyalgia syndrome" strongly recommends Qigong, Tai Chi, and yoga for the FM treatment [36].…”
Section: Exercisesmentioning
confidence: 97%